Professional tennis`s constellational response to COVID-19 - King, K. R. (International Journal of Sport Communication, 2020)
Tennis`s dispersed power relations have made its semiorganized response to COVID-19 "constellational" rather than hierarchical. The author uses the term "constellational" in two senses. First, what might appear to be a disorganized set of stars in the night sky can, with a bit of orientation, be tracked into discernible and more meaningful patterns. In tennis, constellations are clusters of tour events that are linked through geography, court surface, governing bodies, key sponsors, and other forms of patronage. Second, the author invoked the language of "constellations" to draw upon the popular connotation of "stars": iconic figures on- and off-court who speak and act in ways that carry outsize importance to the game`s audience. This constellational set of power relations has led to conflicted messaging—only sometimes valuing public health. Both prestigious tournaments and star players have emerged as important stakeholders, as tennis assesses its future—and organizational structure—postpandemic.